Presence and structure‐activity relationship of intrinsically disordered regions across mucins. Issue 2 (5th January 2020) - Carmicheal, Joseph; Atri, Pranita; Sharma, Sunandini; Kumar, Sushil; Chirravuri Venkata, Ramakanth; Kulkarni, Prakash; Salgia, Ravi; Ghersi, Dario; Kaur, Sukhwinder; Batra, Surinder K.
Abstract: Many members of the mucin family are evolutionarily conserved and are often aberrantly expressed and glycosylated in various benign and malignant pathologies leading to tumor invasion, metastasis, and immune evasion. The large size and extensive glycosylation present challenges to study the mucin structure using traditional methods, including crystallography. We offer the hypothesis that the functional versatility of mucins may be attributed to the presence of intrinsically disordered regions (IDRs) that provide dynamism and flexibility and that the IDRs offer potential therapeutic targets. Herein, we examined the links between the mucin structure and function based on IDRs, posttranslational modifications (PTMs), and potential impact on their interactome. Using sequence‐based bioinformatics tools, we observed that mucins are predicted to be moderately (20%‐40%) to highly (>40%) disordered and many conserved mucin domains could be disordered. Phosphorylation sites overlap with IDRs throughout the mucin sequences. Additionally, the majority of predicted O ‐ and N ‐ glycosylation sites in the tandem repeat regions occur within IDRs and these IDRs contain a large number of functional motifs, that is, molecular recognition features (MoRFs), which directly influence protein‐protein interactions (PPIs). This investigation provides a novel perspective and offers an insight into the complexity and dynamic nature of mucins.